Desert dispute : the diplomacy of boundary-making in south-eastern Arabia. - KELLY, J. B. (Gulf studies., 2019)
This new and previously unpublished study, by the foremost authority on the subject, is an exhaustive one, based on thorough research in the relevant archives and direct experience of the dispute. As such it will be the standard reference work on this question for all who have an interest in the Gulf Arab states, their territorial origins and its effects on their increasing role in regional and world affairs. The struggle to delineate the boundaries of south-eastern Arabia can claim to be one of the longest running diplomatic disputes of the twentieth century, which has echoes to this day. Vol.